2018
DOI: 10.1242/dev.157149
|View full text |Cite
|
Sign up to set email alerts
|

EED, a member of the polycomb group, is required for nephron differentiation and the maintenance of nephron progenitor cells

Abstract: Epigenetic regulation of gene expression has a crucial role allowing for the self-renewal and differentiation of stem and progenitor populations during organogenesis. The mammalian kidney maintains a population of self-renewing stem cells that differentiate to give rise to thousands of nephrons, which are the functional units that carry out filtration to maintain physiological homeostasis. The polycomb repressive complex 2 (PRC2) epigenetically represses gene expression during development by placing the H3K27m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
2
14
0
Order By: Relevance
“…The results of this work as well as previous works suggest that epigenetic mechanisms play a role in kidney development [ 30 , 40 , 41 , 42 , 43 , 44 , 45 ]. Therefore, we wanted to systematically evaluate the effect of epigenetic modulators of the different enzyme classes on renal development.…”
Section: Resultssupporting
confidence: 84%
“…The results of this work as well as previous works suggest that epigenetic mechanisms play a role in kidney development [ 30 , 40 , 41 , 42 , 43 , 44 , 45 ]. Therefore, we wanted to systematically evaluate the effect of epigenetic modulators of the different enzyme classes on renal development.…”
Section: Resultssupporting
confidence: 84%
“…We speculate that these maturational changes in chromatin accessibility are likely orchestrated by concomitant changes in the epigenetic machinery such as the Polycomb complex, ATP-dependent chromatin remodelers, DNA methylation and the NuRD/HDAC complex, that govern the access of master regulators to their cis-acting elements. Indeed, there is genetic evidence that perturbations of the epigenetic machinery disrupt the balance between NPC proliferation and differentiation in vivo (Denner and Rauchman, 2013; El-Dahr and Saifudeen, 2018; Liu et al, 2018; Zhang et al, 2018). A caveat in this study is that ChIP-seq was performed on E13 and P0 NPC cultured in NPEM for two passages.…”
Section: Discussionmentioning
confidence: 99%
“…Eed KO resulted in smaller kidneys and premature loss of NPCs, and the investigators revealed a dual role of PRC2: it is required to maintain self-renewal of the NPCs; during differentiation, it might also be involved in repressing self-renewal genes, like Six2, to facilitate proper nephron differentiation. 15 However, the direct target genes regulated by PRC2 remains to be determined.…”
Section: Significance Statementmentioning
confidence: 99%